Practicality of E-Modules Based on Differentiated Learning and Flipbook Technology in Al-Qur'an Hadith Instruction - Salman Yafi; Sasmi Nelwati; Muhammad Kosim; Milya Sari; Radhiatul Hasnah (AL-ISHLAH: Jurnal Pendidikan, 2025)
The integration of differentiated learning with digital technologies such as Flipbook offers new opportunities for inclusive instruction, particularly in Islamic education. This study investigates the practicality of E-Modules designed with differentiated learning principles and Flipbook technology in the teaching of Al-Qur’an Hadith at the Madrasah Tsanawiyah (MTsN 3 Padang). Using a mixed-methods approach, the study involved one educator and 24 students. Quantitative data were gathered via practicality questionnaires, while qualitative input was collected through open-ended feedback. Quantitative data were analysed descriptively, and qualitative responses were processed using thematic analysis. Findings show that the E-Module is considered highly practical, with an overall practicality score of 82% from educators and 85% from students. Users highlighted ease of navigation, clarity of instructions, and the effectiveness of interactive features such as quizzes and videos. However, both groups identified areas for improvement—especially in content readability, font size, and visual layout. The results suggest that Flipbook-assisted, differentiated E-Modules effectively support learning in Islamic education settings. They accommodate various learning styles and enhance engagement. Nevertheless, improvements in design and content presentation are recommended. This study addresses a gap in Islamic learning media research and contributes to the development of inclusive, technology-integrated instruction. With refinements addressing readability and learner diversity—including readiness, interests, and talents—such E-Modules hold strong potential as effective tools in Qur’anic Hadith education.